Eros/Cupid from a cave shrine in the ancient «Carmo» (Carmona, Sevilla). Archaeological and iconographical analysis of a Roman gemstone - María LIMÓN BELÉN; Juan Manuel ROMÁN RODRÍGUEZ (Zephyrus, 2015)
The aim of this paper is to study a Roman intaglio from a cave shrine discovered in Carmona (Sevilla). It is carved in carnelian and contains the image of a winged young man holding a torch with both hands that can be identified as Eros/Cupid. Firstly, the analysis of this exceptional specimen based on its typological classification is undertaken. After that, the iconography of Eros/Cupid through the Classical texts, his role in Classical mythology and its representation in Ancient art is studied with a focus on Eros the torchbearer. Finally, an interpretation of the object based on the data provided by the archaeological context is offered. The archaeological context allows the intaglio to be dated before Vespasian times. The gem and other objects found in the same context are interpreted as possible offerings preceding the end of the activity of the sanctuary.